2005
DOI: 10.1007/s00415-005-0819-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characteristics of cortical malformations causing epilepsy

Abstract: Purpose-Cortical malformations (CMs) are increasingly recognized as the epileptogenic substrate in patients with medically refractory neocortical epilepsy (NE). The aim of this study was to test the hypotheses that: 1. CMs are metabolically heterogeneous. 2. The structurally normal appearing perilesional zone is characterized by similar metabolic abnormalities as the CM.Methods-Magnetic resonance spectroscopic imaging (MRSI) in combination with tissue segmentation was performed on eight patients with NE and CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
5
21
0
5
Order By: Relevance
“…In 11 of these articles, the metabolite ratios obtained in the lesion were compared with those in a control group, and in 9 articles, the NACS was also studied. 9,19,20,[24][25][26][27]29 The abnormality most frequently found in MCD was decreased NAA or NAA/Cr in the lesion compared with a that in the control group, 9,20,[22][23][24]27,28,31 in agreement with our results, but some articles reported cases presenting a normal NAA peak in MCD compared with that in a control group. 21,29,30 This observation might be explained by the fact that these authors used single-voxel MR spectroscopy with a larger voxel volume size (3-8 cm 3 ) than the one used in our study (2.25 cm 3 ).…”
Section: Controls Patientssupporting
confidence: 91%
See 2 more Smart Citations
“…In 11 of these articles, the metabolite ratios obtained in the lesion were compared with those in a control group, and in 9 articles, the NACS was also studied. 9,19,20,[24][25][26][27]29 The abnormality most frequently found in MCD was decreased NAA or NAA/Cr in the lesion compared with a that in the control group, 9,20,[22][23][24]27,28,31 in agreement with our results, but some articles reported cases presenting a normal NAA peak in MCD compared with that in a control group. 21,29,30 This observation might be explained by the fact that these authors used single-voxel MR spectroscopy with a larger voxel volume size (3-8 cm 3 ) than the one used in our study (2.25 cm 3 ).…”
Section: Controls Patientssupporting
confidence: 91%
“…5 Previous published studies about MR spectroscopy and MCD are very different in the number of cases and methodologies used. 9,[19][20][21][22][23][24][25][26][27][28][29][30][31] Of these studies, 8 used single-voxel MR spectroscopy and 6 used multivoxel MR spectroscopy. Six are case reports, and in the remaining 8 articles, the number of patients studied varied from 8 to 31.…”
Section: Controls Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical malformations are not only characterized by a disturbed tissue architecture but also by an intrinsic epileptogenicity and those NAA and Cho abnormalities probably reflect both disturbances. (38) …”
Section: Identification Of the Epileptogenic Focusmentioning
confidence: 99%
“…Mueller et al found that metabolic abnormalities in the perilesional zone share the characteristics of MCD and that these abnormalities may be related to areas of microscopic malformations and/or intrinsic epileptogenicity. 12 In addition, MCD are metabolically heterogeneous because they may contain abnormal as well as normal areas. Abnormal diffusion anisotropy has also been found beyond the visualized limits of MCD.…”
mentioning
confidence: 99%